2006
DOI: 10.1111/j.1365-2486.2006.01297.x
|View full text |Cite
|
Sign up to set email alerts
|

Projected changes in the organic carbon stocks of cropland mineral soils of European Russia and the Ukraine, 1990–2070

Abstract: In this paper, we use the Rothamsted Carbon Model to estimate how cropland mineral soil carbon stocks are likely to change under future climate, and how agricultural management might influence these stocks in the future. The model was run for croplands occurring on mineral soils in European Russia and the Ukraine, representing 74 Mha of cropland in Russia and 31 Mha in the Ukraine. The model used climate data from the HadCM3 climate model, forced by four Intergovernmental Panel on Climate Change (IPCC) emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 42 publications
5
36
0
2
Order By: Relevance
“…Table 4 shows that for most of the countries, detectable changes range from 1% to 10% in the base estimate of stock. These changes are very similar to the projected changes (about 6%) simulated by Smith et al (2007) in mineral soil C of European Russia and Ukraine's croplands and grasslands over the last 10 years of their simulation (2060)(2061)(2062)(2063)(2064)(2065)(2066)(2067)(2068)(2069), under the business-as-usual scenario. This suggests that over about 10 years most of the existing SMNs could be used to verify such changes.…”
Section: Discussionsupporting
confidence: 77%
“…Table 4 shows that for most of the countries, detectable changes range from 1% to 10% in the base estimate of stock. These changes are very similar to the projected changes (about 6%) simulated by Smith et al (2007) in mineral soil C of European Russia and Ukraine's croplands and grasslands over the last 10 years of their simulation (2060)(2061)(2062)(2063)(2064)(2065)(2066)(2067)(2068)(2069), under the business-as-usual scenario. This suggests that over about 10 years most of the existing SMNs could be used to verify such changes.…”
Section: Discussionsupporting
confidence: 77%
“…Although climatic extremes are likely to become more frequent and more severe toward the end of the century, the current Earth system models do not simulate adequately the impacts of climate extremes on biogeochemical cycles (47) and still have large uncertainties in parameterizing regional responses to such events and often provide contrasting results (47)(48)(49)(50). Our experiment highlights the importance of accounting for interactions between drivers of global change, their seasonality effects, and the importance of poststress recovery processes for more accurate model predictions of the future C budgets of grasslands.…”
Section: Resultsmentioning
confidence: 99%
“…According to Post et al (2001) extensive changes in land use and agricultural activities which have occurred during the last 200 years have transformed soils into net sources of atmospheric CO 2 . Recent research works have postulated that past changes in land-use history and land management have been the main reasons for the SOC losses, rather than higher temperatures and changes of precipitation resulting from climate change (Bellamy et al, 2005;Gardi and Sconosciuto, 2007;Smith et al, 2007aSmith et al, , 2007bSmith, 2008;Minasny et al, 2010). Smith et al (2007c) reported that only about 10-20% of observed soil carbon losses occurred in England and Wales from 1978 to 2003 could possibly be attributable to climate warming.…”
Section: Introductionmentioning
confidence: 97%